Tattooing and risk for transfusion-transmitted diseases: the role of the type, number and design of the tattoos, and the conditions in which they were performed. - Nishioka, S. de A. (Cambridge University Press, 2002)
Tattoos have been shown to be associated with transfusion-transmitted diseases (TTDs), particularly hepatitis B virus (HBV) and hepatitis C virus (HCV) infections. Very little is known about the association between different categories of tattoos and TTDs. In a cross-sectional study in Brazil, we studied 182 individuals with tattoos and assessed the odds of testing positive for a TTD according to tattoo type, number, design and performance conditions. Major findings were significant associations between an increasing number of tattoos and HBV infection (odds ratio (OR) of 2.04 for two tattoos and 3.48 for > or = 3 tattoos), having a non-professional tattoo and testing positive for at least one TTD (OR = 3.25), and having > or = 3 tattoos and testing positive for at least one TTD (OR = 2.98). We suggest that non-professional tattoos and number of tattoos should be assessed as potential deferral criteria in screening blood donors.